Q: What is x in this equation 3x plus 4 equals -11?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-8

No because: 8+3x=x+11+2x (rewrite equation) 8+3x=11+3x (combine like terms) 8=11 (subtract 3x from both sides) This is obviously a false statement, so there is no solution or answer to the equation.

The discriminant is -11.

x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0

According to my calculations, yes. 2x+8=3x+11 -8 2x=3x+3 -2x 0=x+3 -3 -3=x

Related questions

-8

No because: 8+3x=x+11+2x (rewrite equation) 8+3x=11+3x (combine like terms) 8=11 (subtract 3x from both sides) This is obviously a false statement, so there is no solution or answer to the equation.

It is an equation and the value of x is 12

The discriminant is -11.

x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0

Your answer can be solved by rewriting the equation in point-intercept notation. * -3x + 2y = 11 * 2y = 3x + 11 * y = (3x+11)/2 That line lists all of the possible answers.

According to my calculations, yes. 2x+8=3x+11 -8 2x=3x+3 -2x 0=x+3 -3 -3=x

undefined.

3x + 2y = 8 This is an equation. It could be the equation of a line.

Where is y in the first equation, you put its equivalent (=) -3x + 11 The first equation is then transformed into: 3x + 2*(-3x + 11) = 7. Then you get: 3x + (-6x) + 2*11 = 7 <=> -3x + 22 = 7 <=> 22 - 7 = 3x <=> 3x = 15 <=> x = 15/3 <=> x = 5. Then you substitute the x in the second equation by its equivalent so, (x = 5) y = -3*x + 11 <=> y = -3*5 + 11 <=> y = -15 + 11 <=> y = -4. x = 5. y = -4.

50, 53, 59

(2, 11)